Medical Imaging 2018: Computer-Aided Diagnosis 2018
DOI: 10.1117/12.2293570
|View full text |Cite
|
Sign up to set email alerts
|

ICADx: interpretable computer aided diagnosis of breast masses

Abstract: In this study, a novel computer aided diagnosis (CADx) framework is devised to investigate interpretability for classifying breast masses. Recently, a deep learning technology has been successfully applied to medical image analysis including CADx. Existing deep learning based CADx approaches, however, have a limitation in explaining the diagnostic decision. In real clinical practice, clinical decisions could be made with reasonable explanation. So current deep learning approaches in CADx are limited in real wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The The classification results show that our second stage properly infers the tumor shape from the binary mask of the breast tumor, which was obtained from the first stage (cGAN segmentation). Hence, we have empirically shown that our CNN is focusing its learning on the morphological structure of the breast tumor, while the rest of approaches ( [10], [11], [45], [46]) rely on the original pixel variations of the input mammogram to make the same inference. Moreover, in [32] they used a hybrid strategy in which they include the pixel variability within the mask of breast tumor region to retain the intensity and texture information.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The The classification results show that our second stage properly infers the tumor shape from the binary mask of the breast tumor, which was obtained from the first stage (cGAN segmentation). Hence, we have empirically shown that our CNN is focusing its learning on the morphological structure of the breast tumor, while the rest of approaches ( [10], [11], [45], [46]) rely on the original pixel variations of the input mammogram to make the same inference. Moreover, in [32] they used a hybrid strategy in which they include the pixel variability within the mask of breast tumor region to retain the intensity and texture information.…”
Section: Resultsmentioning
confidence: 99%
“…We have computed the overall accuracy of each method by averaging the correct predictions (i.e., true positive) of the four classes, weighted with respect to the number of samples per class. As shown in Table 3, our classifier yields an overall accuracy of 80%, outperforming the second best results [11,12] Basal-like 5 10 9 13 37…”
Section: Shape Classification Experimentsmentioning
confidence: 86%
See 3 more Smart Citations